The Alzheimer susceptibility gene BIN1 induces isoform-dependent neurotoxicity through early endosome defects. - Lambert, E.; Saha, O.; Soares Landeira, B.; Melo de Farias, A.R.; Hermant, X.; Carrier, A.; Pelletier, A.; Gadaut, J.; Davoine, L.; Dupont, C.; Amouyel, P.; Bonnefond, A.; et al. (Acta neuropathologica communications, 2022)
The Bridging Integrator 1 (BIN1) gene is a major susceptibility gene for Alzheimer's disease (AD). Deciphering its pathophysiological role is challenging due to its numerous isoforms. Here we observed in Drosophila that human BIN1 isoform1 (BIN1iso1) overexpression, contrary to human BIN1 isoform8 (BIN1iso8) and human BIN1 isoform9 (BIN1iso9), induced an accumulation of endosomal vesicles and neurodegeneration. Systematic search for endosome regulators able to prevent BIN1iso1-induced neurodegeneration indicated that a defect at the early endosome level is responsible for the neurodegeneration. In human induced neurons (hiNs) and cerebral organoids, BIN1 knock-out resulted in the narrowing of early endosomes. This phenotype was rescued by BIN1iso1 but not BIN1iso9 expression. Finally, BIN1iso1 overexpression also led to an increase in the size of early endosomes and neurodegeneration in hiNs. Altogether, our data demonstrate that the AD susceptibility gene BIN1, and especially BIN1iso1, contributes to early-endosome size deregulation, which is an early pathophysiological hallmark of AD pathology.